2000
DOI: 10.1046/j.1365-2842.2000.00545.x
|View full text |Cite
|
Sign up to set email alerts
|

Viscoelastic properties of denture base resins obtained by underwater test

Abstract: The viscoelastic properties of denture base polymers, such as poly(methylmethacrylate) (PMMA), polycarbonate (PC), polysulfone (PSF) and polyethersulfone (PES) which have been used in current clinical dentistry were investigated. In addition, water absorption, diffusion coefficient of water into material, cubical expansion, specific volume and residual monomer were also determined. From the results of this study, the viscoelastic behaviours of the denture base polymers in water have been discussed. The relaxat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 15 publications
0
18
0
2
Order By: Relevance
“…It is important because it causes plasticization, lowering of the glass transition temperature (Tg) and may affect the mechanical properties and dimensional stability [30]. It also subjects the material to internal stresses that may result in crack formation and, eventually, fractures [31]. Based on the results of this study, Parylene-C coated PMMA presented with statistically reduced Wsp compared to uncoated PMMA.…”
Section: Water Sorptionmentioning
confidence: 78%
“…It is important because it causes plasticization, lowering of the glass transition temperature (Tg) and may affect the mechanical properties and dimensional stability [30]. It also subjects the material to internal stresses that may result in crack formation and, eventually, fractures [31]. Based on the results of this study, Parylene-C coated PMMA presented with statistically reduced Wsp compared to uncoated PMMA.…”
Section: Water Sorptionmentioning
confidence: 78%
“…The water taken up in polymer acts as plasticizer and leads to decreased mechanical properties. (9,19,20) The results also showed that the microwave curing method gave a higher surface hardness value (112.137±3.02 for Major and 113.175±1.54 for QD) than the water bath curing method for the control groups, without relining (109.85±3.93 for Major and 111.312±2.339 for QD). These results were in agreement with other authors.…”
Section: Surface Hardness Testmentioning
confidence: 82%
“…On this note, Hiromori et al 29) stated that PMMA denture base polymer reaches saturation about 30 days after immersion.…”
Section: Discussionmentioning
confidence: 99%